Evaluasi Kinerja Apotek Cigadung Menggunakan Pendekatan Balance Scorecard: Evaluasi Kinerja Apotek Cigadung Menggunakan Pendekatan Balance Scorecard - Mubarok, Ilham; Listiana, Ina (Jurnal Medika Farmaka, 2025)
Organizational performance (one of which is a pharmacy) can be assessed through various approaches, one of which is the Balance Scorecard (BSC). Measuring pharmacy performance is a crucial aspect of pharmacy growth and development. This study aims to evaluate the performance of Cigadung Pharmacy based on four Balance Scorecard perspectives: financial, customer, internal business processes, and learning and growth. This research is a non-experimental case study with a descriptive approach. A sample of 95 customers was obtained through Purposive Sampling. The results indicate that from a financial perspective, the Net Profit Margin (NPM) is 8%, Return on Investment (ROI) is 47%, and Return on Equity (ROE) is 26%. The customer perspective indicates a satisfactory level of customer satisfaction. The internal business process perspective indicates that the waiting time for prescription services meets the Ministry of Health Regulation standards. The learning and growth perspective also shows quite good results. Conclusion: Cigadung Pharmacy's performance is assessed as good based on the four Balance Scorecard perspectives.Keywords: Pharmacy, Balance Scorecard, Evaluation, Service.